2017
DOI: 10.18805/ijar.v0iof.9141
|View full text |Cite
|
Sign up to set email alerts
|

Immune profiles of T lymphocyte subsets in adipose tissue of obese mouse induced by high-fat diet

Abstract: In this study, we analyzed high-fat diet (HFD)-induced time-course changes in proportions of T lymphocyte subsets in adipose tissue.Mice were fed with normal-fat diet (NFD) or HFD for 20 weeks. An autoanalyzer was used to assay plasma concentrations of glucose, cholesterol, triglycerides, low-density lipoprotein (LDL), and high-density lipoprotein (HDL). Stromal vascular cells were isolated from epididymal adipose tissues and labeled with antibodies for cluster of differentiation (CD) 3, CD4, CD8, interferon -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
1
1
Order By: Relevance
“…There were evidences that serum levels of the proinflammatory SAA were moderately increased in DIO rats (Uhlar and Whitehead, 1999;Dimitrov et al, 2015). Other studies reported alteration of immune profile of rodents in response of high fat diet (Guojun Zhang et al, 2017). Our experiments have shown no significant difference between the SAA levels in obese, compared with control animals.…”
Section: General Time Distribution Of Survival In Groupscontrasting
confidence: 58%
“…There were evidences that serum levels of the proinflammatory SAA were moderately increased in DIO rats (Uhlar and Whitehead, 1999;Dimitrov et al, 2015). Other studies reported alteration of immune profile of rodents in response of high fat diet (Guojun Zhang et al, 2017). Our experiments have shown no significant difference between the SAA levels in obese, compared with control animals.…”
Section: General Time Distribution Of Survival In Groupscontrasting
confidence: 58%
“…Obesity regulates immune cells in adipose tissue ( 22 ). Adipose tissue is a vital immune organ that stores fat and provides energy ( 23 ). Obesity changes the immune cell landscape in adipose tissues, causing the pro-inflammatory cells and CD8+T cells to gradually dominate ( 24 , 25 ).…”
Section: Discussionmentioning
confidence: 99%